Study on Sizes of Bubbles Liquid Flow through a Vertical Pipe - Sulaiman, S. A. (2012)
Multiphase flows such as those in the oil and gas industries complicate the production operation in many ways. Abilities to predict the behavior of such flow may reduce high operational cost and increase productivity. While a real crude oil comprises more than three phases of fluid, experimental simulations of a simplified two-phase flow system may help to understand the flow behavior at fundamental level. In this paper, bubbles diameters in liquid flow at different vertical displacements and flow rates are studied. The study is carried out experimentally on flows of water at 5, 10 and 15 gpm with air bubbles, of which the diameters are measured by using Phase Doppler Anemometer (PDA). It is found that the air bubbles are larger near the pipe wall as compared to those in the central region of the pipe. The bubbles are also observed to become smaller with increase in the water flow rate.